Heart of Darkness: una sesión de logoterapia - Alcón Illanes, Juan (THÉMATA. Revista de Filosofía, 2012)
Presentaremos cómo Joseph Conrad en Heart of Darkness, a través de la sucesiva aparición de personajes, nos mostrará la muerte y la enfermedad ligadas a la experiencia humana traumática. A través de un camino que lleva hacia el corazón de las tinieblas veremos como su obra parece una reivindicación del poder terapéutico de la palabra, la logoterapia. We will present how Heart of Darkness, the Joseph Conrad’s work, across the successive appearance of its main characters, will show us the death and the disease tied to the human traumatic experience. Across a way that goes towards the heart of darkness we will see how it seems to claim the therapeutic power of the word, the logo-therapy.